Short vs. long chains competition during "grafting to" process from melt. Issue 26 (22nd June 2022) - Chiarcos, Riccardo; Antonioli, Diego; Gianotti, Valentina; Laus, Michele; Munaò, Gianmarco; Milano, Giuseppe; De Nicola, Antonio; Perego, Michele
Abstract : A preferential grafting of short chains occurs during the " grafting to " reaction of hydroxy terminated P(S- st -MMA) blends consisting of short and long chains. The enrichment is enhanced when the chain length difference increases. Abstract : Equimolar blends of a partly deuterated hydroxy terminated poly(styrene d8 - st -methyl methacrylate) copolymer with average molecular weight ( M n ) of 11 200 g mol −1 and a hydroxy terminated poly (styrene- st -methyl methacrylate) copolymer with M n ranging from 3600 to 38 600 g mol −1 were thermally grafted from melt to a silicon wafer at 250 °C in N2 atmosphere. Thickness of the brush layers as a function of time was determined by ellipsometry while composition of the brush was determined by TGA-GC-MS. A preferential grafting of the lower molecular weight component of the blend into the polymeric brush was observed and quantified. The enrichment of short chains in the brush layer is essentially independent of time, suggesting that this phenomenon is related to a segregation of short chains close to the polymer/substrate interface occurring before grafting. Molecular dynamics simulations support this idea. Collected data shed new light on the mechanism of the " grafting to " process from melt and indicate that further work is necessary to identify the key parameters that drive the grafting process to prepare brush layers with precisely tuned characteristics.